SELF-REGULATED LEARNING STRATEGIES AND VOCABULARY SIZE AMONG INDONESIAN EFL SENIOR HIGH STUDENTS (RETAIN, 2020)
Self-regulated learning is a learning process that explores the students’ intrinsic factors, such as strategies and motivations. Strategies used by students are different based on their needs. In language learning, students have their strategies to acquire good vocabulary. This present study aimed to describe the self-regulated learning strategies used by the Indonesian EFL senior high students and examine the correlation with the students’ vocabulary size. Quantitative research was carried out on 76 senior high students in Gresik, Indonesia. The sample was collected through convenience sampling. The data were collected through students’ vocabulary level test and self-regulated learning strategies questionnaire. The first finding shows that environmental control was the most used strategies and emotion control was the least used strategy by the students. A descriptive statistic was carried out to describe the result. The second finding indicates there was a significant correlation between strategies used by students and their vocabulary size. Pearson correlation indicates the low negative correlation between those two variables.